2023
DOI: 10.3390/fermentation9080710
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of L-Lysine-α-oxidase Enzyme and Trichoderma harzianum Rifai Culture Liquid on the Formation of Biofilms by Uropathogenic Multiresistant E. coli

Abstract: In this study, the data of the antagonistic action of the enzyme L-lysine-α-oxidase in relation to clinical isolates of multiresistant uropathogenic Escherichia coli isolated from patients aged 2 to 17 years of various genders with an established diagnosis of infectious urethritis and/or cystitis are presented. According to the results obtained, the top priority drugs for the treatment of infectious urethritis and/or cystitis are FO (Fosfomycin, 200 µg/disc), IMP (Imipenem, 10 mg/disc), and CIP (Ciprofloxacin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The plate was incubated for 15 min, washed again with PB solution, and dried for 15 min. After that, 150 µL of 96% ethanol was added to each well, then incubated for 15 min and the result was recorded on the microplate reader at a wavelength of 492 nm [25,43,44]. The average decrease was measured and used to calculate the biofilm inhibition percentage by ATE, where OD AS was the optical density average of C. albicans samples in the experiment and OD AC was the optical density average of isolates in control without ATE:…”
Section: Biofilm Formation Abilitymentioning
confidence: 99%
“…The plate was incubated for 15 min, washed again with PB solution, and dried for 15 min. After that, 150 µL of 96% ethanol was added to each well, then incubated for 15 min and the result was recorded on the microplate reader at a wavelength of 492 nm [25,43,44]. The average decrease was measured and used to calculate the biofilm inhibition percentage by ATE, where OD AS was the optical density average of C. albicans samples in the experiment and OD AC was the optical density average of isolates in control without ATE:…”
Section: Biofilm Formation Abilitymentioning
confidence: 99%
“…A few studies have shown its antitumor [ 20 , 21 ] and antifungal [ 15 , 22 ] activities. Previously, our study demonstrated the effect of LO produced by the fungus Trichoderma harzianum Rifai on the process of biofilm formation in UPEC [ 23 ].…”
Section: Introductionmentioning
confidence: 99%